TRANSFORMATION OF HR MANAGEMENT IN ENTERPRISES (International scientific-electronic journal “Pioneering studies and theories”, 2025)
The article discusses the need to organize effective forms of using employees engaged in official activities to ensure the economic efficiency of creating enterprises in a market economy. In a market economy, the use of innovative technologies in the process of providing services, the role of employees in the process of providing services by the management of enterprises and institutions increases, there is a need to ensure the formation of relations between employees based on market requirements. Personnel management at enterprises depends on the economic policy of the state and each enterprise in the service sector. The main goal of the economic policy of the Republic of Uzbekistan is the formation of an economy based on national traditions, free competition, bringing national products to the level of developed countries in the world market.